Diakästen im Haus in Lissabon (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2014)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Photographs; Lisbon; Accessioning (Works of Art); Cataloging (Works of Art); Classification (Works of Art)